Optimalisasi Manajemen Logistik Puskesmas untuk Meningkatkan Kualitas Layanan Kesehatan di Kabupaten Solok - Tuty Ernawati; Luthfil Hadi Anshari; Mia Fitria (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Effective logistics management in the maintenance and storage of medical equipment plays an important role in ensuring patient safety and supporting service efficiency at community health centers (Puskesmas). However, several Puskesmas in Solok Regency still face challenges such as suboptimal logistics management, limited storage facilities, and inadequate monitoring and evaluation processes. These issues increase the risk of equipment damage, service disruption, and occupational safety hazards for both medical staff and patients. This community service program aimed to strengthen the logistics management capacity of Puskesmas through socialization and training on the implementation of Occupational Health and Safety (OHS) principles and integrated logistics management. The methods included coordination with the Solok District Health Office, training for Puskesmas staff, mentoring in logistics recording, and the provision of educational media such as banners and leaflets. The results showed an improvement in participants’ understanding of logistics management and OHS principles, with more than 80% of participants able to apply proper storage systems and conduct periodic monitoring of medical equipment. In addition, internal coordination in the procurement and distribution of medical equipment at partner Puskesmas improved significantly. This program contributed to enhancing safety, availability, and the quality of health services at Puskesmas, and is expected to serve as an initial step toward developing a sustainable logistics management system in Solok Regency.